Edukasi Digital: Pembelajaran Ilmu Agama Islam Melalui Kanal Youtube Dalam Pandangan Tradisi Ilmu Sanad - Azkia Falsa Annaba; Komarudin Soleh (Pendidikan Agama Islam STAIPI Persis Bandung, 2022)
The hectic movement off all aspects of life from traditional to modern with digitalization has made a very significant change in education , known as the digitalization of education. It contains several applications that help and make it easier for education actors to spread their knowledges but with this convenience it can provide the possibility of users accessing independently to get knowledge, without guidance, directly by a teacher, thus allowing accesors to think without direct direction from the teacher directly. From this situation, the situation is very different from the Sanad Science tradition which requires teachers and students to meet face-to-face, but with the current digital situation making it easy for access to study anywhere and to anyone, it is very important how the views of sanad science on the problem can become a measure for education actors, especially students or students, can be directed to proper education and is not mistaken even though they do not meet directly with the teacher concerned. The research method uses descriptive qualitative research methods whose results are non-numerical, by linking to several aspects of the theory that are relevant to the problem so that some conclusions can be drawn from the theory developed by reviewing aspects of the problem.